Analyzing the use of ICT in demand and access to information and services for pastoralists - Khalai, D.; Banerjee, Rupsha R.; Mude, Andrew G. (International Livestock Research Institute, 2016)
Index Based Livestock Insurance in the Arid and Semi-Arid Land (ASALs) of Northern Kenya and Southern Ethiopia is being implemented by the International Livestock Research Institute (ILRI), as a drought coping mechanism, anchored on the belief that development of an insurance scheme for livestock in a pastoral setting could be an effective risk-management strategy. The contracts are designed using low cost, accessible and reliable satellite data; Normalized Differenced Vegetation Index (NDVI). The payouts ensure that the animals are kept alive instead of providing payouts to replace / restock potentially dead animals. One of ILRI's commercial partners, Takaful Insurance of Africa (TIA) uses community shop agents in the distribution of the IBLI product. This approach is based on an agency model for providing financial services such as micro- insurance. Accurate, reliable and timely information, enable pastoralists to make better decisions on the kinds of feeds, animal health and marketing decisions; particularly where to sell and buy animals and negotiate better prices. Though ICT in developing countries have become a major means of disseminating information, both pastoralists and organisations working in the ASALs of Kenya have not yet fully taken advantage of the available cutting edge scientific techniques. This study therefore sought to understand how mobile technology through an agency model can be leveraged for crowd-sourcing and dissemination of information important for marketing livestock, livestock products and services. Key informant interviews and focused group discussions were carried out with the different actors from the private sector, public sector and the pastoralists. Isiolo County was chosen as the study site. Some of the key findings suggest that most efforts to use ICTs in collection and dissemination of information have failed in contexts that have no other support mechanisms around the pastoralist. Secondly, an agent in the form of drought monitors, food monitors, Community Animal Health Workers and Government administrators', are vital support to phone based approaches in collection and dissemination of information. Further investigations are needed to understand how these entities can be used to implement an effective ICT based market information system, leading to sustainable and food secure livelihoods in the ASALs.